2017
DOI: 10.1007/s11356-017-9502-7
|View full text |Cite
|
Sign up to set email alerts
|

Time series analysis of ambient air pollution effects on daily mortality

Abstract: Although the growths of ambient pollutants have been attracting public concern, the characteristic of the associations between air pollutants and mortality remains elusive. Time series analysis with a generalized additive model was performed to estimate the associations between ambient air pollutants and mortality outcomes in Shenzhen City for the period of 2012-2014. The results showed that nitrogen dioxide (NO)-induced excess risks (ER) of total non-accidental mortality and cardiovascular mortality were sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…Nonlinear exposure-lag-response relationships have been demonstrated between outdoor air pollution and multiple health outcomes (Chen et al, 2017;Guo et al, 2017). The distributed-lag nonlinear model (DLNM) is an advanced time-series analysis method proposed by Gasparrini (Gasparrini, 2011;Gasparrini et al, 2010), that has been widely used to explore the relationships between meteorological factors and health outcomes (Buteau et al, 2018;Gasparrini, 2014;Neophytou et al, 2018), but has seldom been applied to evaluate the relationship between outdoor exposure to air pollution and active TB risk.…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear exposure-lag-response relationships have been demonstrated between outdoor air pollution and multiple health outcomes (Chen et al, 2017;Guo et al, 2017). The distributed-lag nonlinear model (DLNM) is an advanced time-series analysis method proposed by Gasparrini (Gasparrini, 2011;Gasparrini et al, 2010), that has been widely used to explore the relationships between meteorological factors and health outcomes (Buteau et al, 2018;Gasparrini, 2014;Neophytou et al, 2018), but has seldom been applied to evaluate the relationship between outdoor exposure to air pollution and active TB risk.…”
Section: Introductionmentioning
confidence: 99%
“…A study in Taipei found significant correlations between short‐term exposure to PM2.5 and increased hospital admissions for ischemic stroke on warm (>23°C) and cool days (<23°C) . Guo et al demonstrated that NO 2 , SO 2 , and PM10 had adverse effects on the total non‐accidental mortality and cardiovascular mortality in Shenzhen, especially for men and the elderly during hot seasons . Montresor‐López et al observed a strong correlation between ozone and the risk of hospitalization for stroke …”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have also demonstrated that short‐term exposure to PM2.5 and PM10 (particulate matter with a grain size of 2.5 and 10 μm or less, respectively) increased the risk of ischemic and hemorrhagic stroke . Similarly, NO 2 and PM10 are significantly associated with cardiovascular mortality, with increasing concentrations of NO 2 noted to have a greater impact on cardiovascular mortality in men and the elderly . In addition, the rate of mortality from a stroke varies significantly across seasons; many studies have, therefore, investigated the seasonality of correlations between air pollution and cardiovascular mortality.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations